Analisis Kuat Tekan dan Fleksibel Beton Serat Polyamide/Nylon dengan Campuran Serbuk Kaca Menggunakan Curing Air Laut : Compressive Strength and Flexible Strength Analysis of Polyamide/Nylon Fiber Concrete Mixed with Glass Powder Using Seawater Curing - Manurung, Melki Ridwan; Hutabarat, Lolom Evalita; Setiyadi (Universitas Muhammadiyah Jember, 2023)
In tropical countries surrounded by water, coastal development initiatives are unavoidable. Because chloride compounds (Cl) in seawater are corrosive to concrete and interact directly with seawater, using concrete in coastal locations requires careful consideration—adding pozzolan-like glass powder to concrete results in minimal water absorption. Nylon fiber, on the other hand, is abrasion-resistant and can boost the flexural strength of concrete. In line with SNI 7656-2012, this study used fresh and sea water to maintain test specimens 15 cm wide, 15 cm long, and 60 cm high with a design f'c strength of 25 MPa at 14 and 28 days. The compressive strength increased by 27.9 MPa, and the flexural strength increased by 29.2 MPa after 14 days and 28 days of drying in clean water with 1% fiber variation, respectively. In seawater, the compressive strength at 14 days is 26.5 MPa, the flexural strength at 28 days is 28.8 MPa, and the flexural strength at 28 days is 2,773 MPa and 3,312 MPa. Concrete cured with sea water is lower than concrete treated with fresh water. On the other hand, adding polyamide/nylon to concrete containing glass powder can reduce compressive strength loss by up to 4%.